2016
DOI: 10.1016/j.ijpharm.2016.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Berberine as a photosensitizing agent for antitumoral photodynamic therapy: Insights into its association to low density lipoproteins

Abstract: Recent years have seen a growing interest in Berberine, a phytochemical with multispectrum therapeutic activities, as anti-tumoral agent for photodynamic therapy (PDT). In this context, low density lipoproteins (LDL) play a key role in the delivery of the photosensitizer in tumor cells. We correlate the physicochemical parameters of the berberine association to LDL with the influence of LDL-delivery on its accumulation in a glioma cell line and on its photo-induced activity in view of antitumor PDT. Our result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(40 citation statements)
references
References 51 publications
(53 reference statements)
0
39
0
1
Order By: Relevance
“…174 The PI3K-Akt and mitogen-activated protein kinase (MAPK) signaling pathways in the treatment of thyroid carcinoma also were affected. 175,176 A related isoquinoline alkaloid, coptisine (165), also affected PI3K/Akt and mitochondrial-associated apoptotic pathways, 177 and exhibited remarkable cytotoxic activities against HCT-116 cells by activating the caspase protease family, inducing G1-phase cell cycle arrest and increasing apoptosis. 178 The protoberberine alkaloid palmatine (166) induced cell apoptosis in MCF-7 breast cancer cells; after the treatment (1 μM, 10.8 J/cm 2 ), the early apoptotic and late apoptotic rates increased significantly up to 21.16% and 9.86% in photodynamic therapy.…”
Section: Various Isoquinoline Alkaloidsmentioning
confidence: 99%
“…174 The PI3K-Akt and mitogen-activated protein kinase (MAPK) signaling pathways in the treatment of thyroid carcinoma also were affected. 175,176 A related isoquinoline alkaloid, coptisine (165), also affected PI3K/Akt and mitochondrial-associated apoptotic pathways, 177 and exhibited remarkable cytotoxic activities against HCT-116 cells by activating the caspase protease family, inducing G1-phase cell cycle arrest and increasing apoptosis. 178 The protoberberine alkaloid palmatine (166) induced cell apoptosis in MCF-7 breast cancer cells; after the treatment (1 μM, 10.8 J/cm 2 ), the early apoptotic and late apoptotic rates increased significantly up to 21.16% and 9.86% in photodynamic therapy.…”
Section: Various Isoquinoline Alkaloidsmentioning
confidence: 99%
“…16 Though it is reported that berberine can release ROS by photodynamic therapy, our research showed that both BBR cavitation and ROS can be driven by sonodynamic therapy in vivo. 17,18 All the information we gained in this study indicates that BBRNPs-SDT might present a promising and better noninvasive tumor therapy approach for both preclinical and clinical cancer studies.…”
Section: Introductionmentioning
confidence: 92%
“…Furthermore, alkaloids induce the formation of intracellular ROS in cancer cells, which leads to the destruction of cancer cell metabolism [ 140 , 141 , 142 , 143 ]. The photochemically best-known alkaloid is berberine; Luiza Andreazza et al [ 146 ], Bhattacharyya et al [ 147 ] and Inbaraj et al [ 81 ] reported the antitumour activity of berberine upon UV and blue light irradiation. The irradiation of berberine at 410 nm proved to be effective in controlling brain cancer cell growth [ 146 ].…”
Section: Natural Photoactive Compounds From Plantsmentioning
confidence: 99%
“…The photochemically best-known alkaloid is berberine; Luiza Andreazza et al [ 146 ], Bhattacharyya et al [ 147 ] and Inbaraj et al [ 81 ] reported the antitumour activity of berberine upon UV and blue light irradiation. The irradiation of berberine at 410 nm proved to be effective in controlling brain cancer cell growth [ 146 ]. Beta-carboline and harmine are also a noticeable alkaloid with a photoactive nature and are reported to produce a significant amount of ROS after irradiation [ 148 ], which is considered an important feature of potent PSs.…”
Section: Natural Photoactive Compounds From Plantsmentioning
confidence: 99%